2013
DOI: 10.1007/s11665-013-0690-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Erosion Observed in Electrohydraulic Discharges Used in Pulsed Sheet Metal Forming

Abstract: In this paper, we present results of electrode durability testing and electrode design in a pulsed electrohydraulic discharge environment. Pulsed electrohydraulic forming (EHF) is an electrodynamic process based upon high-voltage discharge of capacitors between two electrodes positioned in a fluid-filled chamber. EHF enables a more uniform distribution of strains, widens the formability window, and reduces elastic springback in the final part when compared to traditional sheet metal stamping. This extended for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Furthermore, it is well known that electrical breakdown in water is accompanied by very large erosion (e.g. ∼100 μm to ∼2 mm) of electrodes; 32,33) thus, one usually has to take special care to keep the inter-electrode gap at the same value. However, since the gap before and after in our experiment was of the same order, we consider that the change of the gap due to erosion did not affect our experiment very much, although we consider that erosion may cause Cu to adhere to the inside of the tube, making [circles; data in Fig.…”
Section: W 2 Dependencementioning
confidence: 99%
“…Furthermore, it is well known that electrical breakdown in water is accompanied by very large erosion (e.g. ∼100 μm to ∼2 mm) of electrodes; 32,33) thus, one usually has to take special care to keep the inter-electrode gap at the same value. However, since the gap before and after in our experiment was of the same order, we consider that the change of the gap due to erosion did not affect our experiment very much, although we consider that erosion may cause Cu to adhere to the inside of the tube, making [circles; data in Fig.…”
Section: W 2 Dependencementioning
confidence: 99%
“…The waves generator consists of a discharging tank and two electrodes. Bonnen et al [19] have shown that electrodes erosion is a significant phenomenon of degradation of the wave generator in electrohydraulic processes. Even if the pointed geometry is the most efficient since it permits to intensify the electric field by point effect [24], 100C6 steel electrodes whose end is cylindrical (diameter 8 mm) were preferred in this study.…”
Section: Waves Generatormentioning
confidence: 99%
“…The electrohydraulic forming process consists in discharging the electrical energy stored in a series of capacitors between two immersed electrodes in a water tank, and to exploit its effects. This discharge creates an electric arc in the water [19], then a plasma, which generates pressure waves that travel in the water. A few microseconds after the discharge, a so-called primary shock wave first appears, followed by a set of so-called secondary pressure waves a few tens of microseconds later, which result from the oscillation of a vapor bubble.…”
Section: Introductionmentioning
confidence: 99%
“…Various scientific articles specifically addressed these issues. It can be cited as an example [21,22]. Furthermore, controlling pressure waves was crucial to enhance process efficiency [13].…”
Section: Main Technical Limitations and Objectives Of This Studymentioning
confidence: 99%
“…Furthermore, controlling pressure waves was crucial to enhance process efficiency [13]. Recent studies aimed to increase the number of electrodes in tooling and explore different chamber shapes and process sequences like in [10,23,24] to improve the efficiency of pressure wave actions on the workpiece. The influence of pulse duration was also emphasized in the literature by [13].…”
Section: Main Technical Limitations and Objectives Of This Studymentioning
confidence: 99%